Addressing Taxonomic and Geographic Biases in ethnozoological studies on animal use in Brazil - Santos, Suellen da Silva Santos; Hyago Keslley de Lucena Soares; Henrique Fernandes Magalhães; Eraldo Medeiros Costa Neto; Fabio de Oliveira Roque; Davidson Gomes Nogueira; Reinaldo Farias Paiva de Lucena (Ethnobiology and Conservation, 2024)
This study aims to assess the current state of ethnozoological research in Brazil. Sistematic review was conducted using the Web of Science and Scopus databases, encompassing all publications available until December 2022. The selected articles, written in various languages, consist of data obtained directly by the researcher, offering taxonomic descriptions of species and their respective uses. 85 articles were selected to construct a distribution map of ethnozoological studies, categorizing them based on their use. The Spearman’s correlation test and the Kruskal-Wallis test, were applied to identify patterns within the data on use, number of studies and zoological class. Spearman’s correlation indicated a positive relationship between the sum of uses and the number of studies conducted. The Kruskal-Wallis test revealed variations in the average number of studies and total uses across different zoological classes. The thematic classification of articles included general ethnozoology, specialized ethnozoology, general medicinal use, specific medicinal use, and hunting. Results showed a consistent increase in publications, with the Northeast region and the Caatinga biome featuring prominently. The reviewed papers encompassed 829 species, demonstrating greater representation in the food and medicinal categories. Ichthyofauna and avifauna, exhibited the highest species number. Our study highlights the utilitarian versatility of herpetofauna and mammal fauna. The classes Asteroidea, Bivalvia, Chilopoda, Echinoidea, and Hydrozoa, were identified as having below-average representation in terms of studies and use associations. In conclusion, the revision advocates for investigations with a collaborative bias among research groups from different biomes, to aid in reducing centralized studies in specific geographical areas.